Sweat characteristics of cramp-prone and cramp-resistant athletes - Miller, K. C.; McDermott, B. P.; Yeargin, S. W. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
Exercise-associated muscle cramps (EAMCs) are thought to be caused by dehydration and/or electrolyte losses. In this multicenter, cross-sectional study, the authors determined whether sweat rates (SRs), sweat electrolyte concentrations, or sweat electrolyte content differed in athletes with (i.e., crampers) and without (i.e., noncrampers) a history of EAMCs and whether these variables could predict EAMC-prone athletes. Male and female collegiate athletes (N = 350) from 11 sports with (n = 245) and without (n = 105) a self-reported history of EAMCs completed a typical exercise or conditioning session. SRs, calculated from body mass, and posterior forearm sweat were analyzed for sweat sodium concentration ([Na+]sw), sweat potassium concentration ([K+]sw), and sweat chloride concentration ([Cl-]sw). The authors used SRs and sweat electrolyte concentrations to calculate sweat electrolyte content lost. Within each gender, no differences in SRs (204 males, p = .92; 146 females, p = .24); [Na+]sw (191 males, p = .55; 126 females, p = .55); Na+sw content (191 males, p = .59; 126 females, p = .20); [K+]sw (192 males, p = .57; 126 females, p = .87); K+sw content (192 males, p = .49; 126 females, p = .03); [Cl-]sw (192 males, p = .94; 77 females, p = .57); and Cl-sw content (192 males, p = .55; 77 females, p = .34) occurred between crampers and noncrampers. Receiver operating characteristic curve analysis revealed that sweat electrolyte content and SRs were predictive of EAMC-prone athletes in American football (area under curve = 0.65-0.72, p = .005), but not in any other sport. EAMCs may not be solely caused by fluid or electrolyte losses in most athletes. Fluid and electrolyte replacement may help American footballers. Clinicians should individualize fluid and electrolyte replacement and understand different etiologies for EAMCs.